Raymond Williams' Reading of Newman's The Idea of a University - Phillips, Jacob (New blackfriars, 2021)
This article engages with an example of Newman's reception in 20th Century thought, in Raymond Williams's Culture and Society from 1958. Williams considers that Newman's wording in The Idea of a University demonstrates a particular moment in the development of the semantic field of the word ‘culture’, which is indicated by the fact Newman does not use the word at an important juncture in his text. Williams also locates Newman in a developing trajectory of English understandings of culture at a point when (what we now term) culture was presented as a surrogate religion. Both of these points are responded to by showing that the word ‘culture’ would not have served the purpose Williams apportions to it for Newman's argument, and that Newman should not be associated with those for whom the domain of culture was emerging as an alternative to religion in the 19th Century. Moreover, this analysis will show that Newman's understanding of what we today term ‘culture’ should be understood in terms of a broader semantic cluster best captured by the word “sensibility”: a set of pervasive tendencies, predispositions, and qualities.